METHODS FOR REMOVING THE PSYCHOLOGICAL BARRIER WHEN MASTERING LANGUAGE MATERIAL - Khojakhanova Munira Abdukakhkharovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article discusses various methods aimed at eliminating psychological barriers that impede the acquisition of language material. Language acquisition is a complex process that is influenced by various cognitive and emotional factors. Understanding and addressing these barriers is critical to promoting effective language learning. The article reviews the existing literature on psychological barriers to language acquisition and presents a comprehensive analysis of strategies to overcome them. Methods include cognitive, affective and practical approaches, providing a holistic view of improving language learning outcomes.